Synonymic notes in the Southeast Asian genus Lutera Westwood, 1875 (Coleoptera: Scarabaeidae: Rutelinae) - Xu, Hao; Zhao, Ming-Zhi (Zootaxa, 2024)
To resolve the taxonomic confusion surrounding two Asian Rutelinae species, Lutera nigromaculata Ohaus, 1900 and L. nigrita Ohaus, 1930, all primary types of relevant taxa have been revisited. A redescription of L. nigromaculata is given, and diagnosis and color illustrations are provided for both L. nigromaculata and L. nigrita. Parastasia ohausi Chûjô, 1966 (new synonym), an unnecessary replacement name for and junior objective synonym of L. nigromaculata, was found in a neglected publication by the late Michio Chûjô. A lectotype is designated for L. nigromaculata guttata (Frey, 1970) (new synonym) which is recognized as another junior synonym of L. nigromaculata. All known distribution records of the two species are mapped, and L. nigromaculata is newly recorded from India and Vietnam. The exact location of “Lakhon” in Indo-China, which is currently Nakhon Phanom of Thailand, is also discussed.